CHANGES IN ARTERIAL BLOOD PRESSURE IN PATIENTS WITH VIRAL HEPATITIS: CLINICAL AND PATHOPHYSIOLOGICAL PERSPECTIVES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Viral hepatitis is a widespread infectious disease affecting the liver parenchyma and leading to systemic metabolic and hemodynamic disturbances. Although hepatic injury is primarily associated with abnormalities in bilirubin metabolism, coagulation, and inflammation, alterations in arterial blood pressure (BP) remain underinvestigated. This study aims to assess arterial BP changes in patients with acute and chronic viral hepatitis, evaluate contributing mechanisms, and identify clinical correlations with liver dysfunction. A total of 120 patients were examined and divided into hepatitis A, B, and C groups. Blood pressure, biochemical parameters (ALT, AST, bilirubin), and markers of hepatic synthetic function were recorded. Results demonstrated a significant trend toward reduced systolic and diastolic BP in moderate and severe hepatitis, whereas mild hepatitis showed stable or slightly increased BP